On the Equivalence of Some Conditions for Convex Functions - Tikhonov, S. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study classes of convex functions on (1, ∞) that tend to zero at infinity. Relations between different elements of these classes are determined.